The development of the Metabolic-associated Fatty Liver Disease during pharmacotherapy of mental disorders – a review - Rogalski, Jakub Krzysztof; Subdys, Aleksandra; Gawlik-Kotelnicka, Oliwia Ewa (Current Problems of Psychiatry, 2022)
Introduction. Metabolic-associated Fatty Liver Disease (MAFLD) is a term for Non-alcoholic Fatty Liver Disease (NAFLD) that highlights its association with components of the Metabolic Syndrome (MetS). MAFLD is becoming a clinically significant problem due to its increasing role in the pathogenesis of cryptogenic cirrhosis of the liver.Material and methods. The resulting work is a review of the most important information on the risk of MAFLD development in the context of the use of particular groups of psychotropic drugs. The study presents the epidemiology, with particular emphasis on the population of psychiatric patients, pathophysiology and scientific reports analyzing the effect of the psychotropic medications on MAFLD development.Results. The drugs that can have the greatest impact on the development of MAFLD are atypical antipsychotics, especially olanzapine, and mood stabilizers (MS) - valproic acid (VPA). Their effect is indirect, mainly through dysregulation of organism's carbohydrate and lipid metabolism.Conclusions. The population of psychiatric patients is particularly vulnerable to the development of MAFLD. At the root of this disorder lies the specificity of mental disorders, improper dietary habits, low level of physical activity and tendency to addictions. Also, the negative impact of the psychotropic drugs on the systemic metabolism indirectly contributes to the development of MAFLD. In order to prevent fatty liver disease, it is necessary to monitor metabolic and liver parameters regularly, and patients should be screened by ultrasound examination of the liver. There are also important preventive actions from the medical professionals, including education of patients and sensitizing to healthy lifestyle.